Vascular dysfunction is associated with major adverse cardiovascular events in prediabetes: A cohort study - Dariya Kozlova; Colin Gimblet; Linder Wendt; Sadaf Akbari; Adeyinka Taiwo; Sanjana Dayal; Patrick Ten Eyck; Anna Stanhewicz; Joel Trinity; Diana Jalal (PLoS ONE, 2025)
Background Prediabetes is a growing public health concern that increases the risk of major adverse cardiovascular events (MACE). Vascular dysfunction worsens with hyperglycemia and is associated with MACE in several high-risk populations. However, it is unknown whether vascular dysfunction contributes to MACE in prediabetes. We hypothesized that vascular dysfunction is associated with elevated risk of MACE in prediabetes. Methods We conducted an observational study of 5742 adults (age 54.9 ± 11.5 years, 54% female) in the Framingham Offspring and Generation III cohorts. Prediabetes was defined using the ADA criteria. Endothelial function was determined via brachial artery flow-mediated dilation (BA-FMD), aortic stiffness via carotid-femoral pulse wave velocity (cfPWV), and coronary artery calcium (CAC) score via computed tomography. Stepwise selection models evaluated BA-FMD, cfPWV, and CAC score by prediabetes status. The association of BA-FMD, cfPWV, and CAC score with time to MACE was assessed via Cox proportional hazards regression. Results Individuals with prediabetes had lower BA-FMD and higher cfPWV and CAC score (p < 0.001). In stepwise selection models, age, sex, smoking history, systolic blood pressure, triglycerides, high-density lipoprotein, low-density lipoprotein, and fasting glucose related to vascular dysfunction. After adjusting for traditional cardiovascular risk factors, BA-FMD (HR [95% CI], 0.93 [0.90,0.97]; p < 0.001) and CAC score >100 [HR [95% CI], 4.15 [2.24, 7.70]; p < 0.001)] were associated with MACE in prediabetes while cfPWV was not (p = 0.051). Conclusions Vascular dysfunction measured by BA-FMD independently associates with MACE in prediabetes. Therapies that target vascular dysfunction may reduce CVD risk in prediabetes.